Granulopoiesis inhibition in acute inflammation: comparative studies in healthy and leukaemic mice - Mohamad Hamood; Francis Corazza; Pierre Francois Bluche; Hassan El Teraifi; Pierre Fondu (Hindawi Limited, 1992)
It was demonstrated previously that mice undergoing an inflammatory reaction induced by subcutaneous (SC) implantation of copper rods, produce humoral factors that initially enhance, but subsequently inhibit, diffusion chamber (DC) granulopoiesis. This provided evidence that granulopoiesis is under the control of both humoral stimulators and inhibitors. In order to test the granulopoietic regulatory mechanism in leukaemic mice, we investigated the regulatory role of granulopoietic humoral inhibitors during in vivo granulopoiesis. We noticed that mice suffering from acute myeloid leukaemia (AML) are unable to augment the production of these humoral inhibitory factors when acute inflammation is induced, since no change in DC cell content was observed with or without prior inflammation. Moreover, unlike healthy mice, the serum of leukaemic mice withdrawn during the inhibition phase of acute inflammation did not show any inhibitory activity toward granulocyte-monocyte (GM) colony growth in vitro. Our results also show that increased levels of normal humoral inhibitors do not influence the proliferation and/or differentiation of leukaemic cells implanted in diffusion chamber cultures.